Collaborative efforts in ASEAN for global asset recovery frameworks to combat corruption in the digital era - Arifin, Ridwan; Riyanto, Sigit; Putra, Akbar Kurnia (Faculty of Law, University of Muhammadiyah Malang, 2023)
In the contemporary digital age, corruption has evolved into a common enemy, transcending borders and becoming a transnational and extraordinary crime. Within the ASEAN framework, corruption is no longer perceived as the concern of a single nation but as a shared threat to all member states and the global community at large. Despite the pervasive and deeply entrenched nature of corruption, concerted efforts have been made to combat this scourge. Among these measures, asset recovery stands out as an extraordinary tool, addressing not only the prevention and enforcement aspects but also the crucial task of repatriating ill-gotten gains to their rightful country of origin. Indonesia and the ASEAN community have entered into various treaties aimed at facilitating asset recovery, with the ASEAN Mutual Legal Assistance Treaty (AMLAT) serving as a pivotal legal instrument in this endeavour. Recognizing the transnational nature of corruption, interstate relations and diplomatic cooperation have assumed a vital role in supporting the success of asset recovery processes. This study explores the evolving landscape of corruption in the digital age, its transformation into a transnational concern, and the collective efforts undertaken within ASEAN to combat it. By focusing on asset recovery as an extraordinary measure, it sheds light on the multifaceted dimensions of eradicating corruption and emphasizes the importance of international collaboration in returning misappropriated assets to their rightful owners.